(untitled) (Conference Zone, 2021)
Literature is a source of knowledge and theories that is comprehensive in all respects, has its own audience, calls people to spiritual maturity, expands their worldview. There are many theories on the coverage of world writers. I am sure that our love for literature will grow once again